Successful Strategies of Japanese Marketing - Alfariz, Muhammad Naufal; Halim, Alfi Nur; Atallah, Restu; Parama, Muhamad Sandi; Luckyardi, Senny; Soegoto, Eddy Soeryanto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Japanese marketing stands out because it keeps companies strong on the world stage, successfully maintaining global standing through a distinctive approach that is deeply rooted in their cultural values and business philosophies all tied to their culture and how they think about business. Unlike Western strategies, which tend to be aggressive and oriented toward short-term gains, the phenomenon of Japanese corporate success lies in prioritizing long-term relationships and consistent quality to build high customer loyalty. This study aims to analyze the key principles of this success. To achieve this, a descriptive qualitative method was employed through a literature review. The results indicate that the integration of Kaizen (continuous improvement), Omotenashi (wholehearted service), and Shinrai (trust) forms a marketing foundation that is superior to competitors. These findings discuss the importance of adapting these philosophies which could help in global competition in creating strategies that could last for long-term.